Le rythme de Bachelard est-il sonore ? - Sauvanet, Pierre (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2024)
Is Bachelard's rhythm a sound? In The Dialectics of Duration, Bachelard distinguishes between the plane of lived life and the plane of the psyche, the latter making it possible to 'resume' the former, in every sense of the word (sewing, repetition and mastery), to give it both coherence and identity. What is interesting here is the way in which Bachelard uses the term rhythm to define this kind of resumption: the rhythm of existence is not real life made up of a succession of moments (because life itself is not rhythmic), it is life lived psychologically, as it is resumed afterwards in the form of a mental rhythm that totalises and organises past moments in the present. But what is the exact status of this mental rhythm: a simple sound metaphor, a more musical reference, or the concept of a purely mental, silent, interiorised rhythm? Rhythm. Time. Duration. Music. Resumption.